2003
DOI: 10.1109/tasc.2003.813918
|View full text |Cite
|
Sign up to set email alerts
|

Differential SFQ transmission using either inductive or capacitive coupling

Abstract: The bias current requirement for RSFQ circuits is about an ampere per thousand gates. High current increases the thermal load of cables into the cryostat, produces undesirable currents and fields on-chip, and makes efficient power supply difficult. Series-biasing has been proposed, whereby the circuit is divided into blocks powered in series. This requires floating ground planes for each block, and differential signal propagation across ground plane boundaries where the blocks communicate. We have demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…A low rate of switching errors in the DFQ driver has been demonstrated in other applications [9], [12], and is expected to apply in this context as well. A speed of 10 Gb/s was expected, but instead was limited to less than 1 Gb/s in test.…”
Section: Discussionmentioning
confidence: 98%
“…A low rate of switching errors in the DFQ driver has been demonstrated in other applications [9], [12], and is expected to apply in this context as well. A speed of 10 Gb/s was expected, but instead was limited to less than 1 Gb/s in test.…”
Section: Discussionmentioning
confidence: 98%
“…Both capacitive (Teh C.K., et al, 2004) and inductive methods (Kang J.H., et al, 2003) of coupling for current recycling have been demonstrated at a small scale. It is difficult to estimate the impact of the technique based on single gate operation as in (Johnson MW et al, 2003). Current recycling becomes easier at higher current density of the superconducting IC (Narayana S 2011).…”
Section: Current Recyclingmentioning
confidence: 99%
“…All these negative effects can be more or less overcome by quantitative improvements of the currently existing RSFQ fabrication technologies and by application of new approaches for design of high-integrated RSFQ digital circuits (Kang and Kaplan, 2003;Johnson et al, 2003). Nevertheless, the design of large synchronous RSFQ circuits meets the speed of light as a fundamental physical limitation about the global synchronization.…”
Section: Basics Of the Rsfq Digital Electronicsmentioning
confidence: 99%